(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The act that leads to the crime of adultery in the conventional sense is any illicit sexual intercourse that occurs consensually between a man and a woman. This crime is considered one of the most dangerous acts of all, as it constitutes a violation of moral principles that do not permit any sexual intercourse outside the framework of a marital relationship, and it constitutes an assault. On the provisions that regulate the lives of individuals, and every sexual relationship outside the framework of this legitimate relationship is considered an assault on the provisions of religion, and it also constitutes a violation of the basic social rules that regulate the lives of individuals, as adultery is considered a great danger to those rules and to the social system, and it finally affects the core of society. Namely, the family. The family cannot perform its social role except within the framework of family cohesion, and this can only be done in light of healthy and legitimate sexual relations or contacts.